Procesos educativos en el uso del servicio de agua potable comunal de la localidad de San Pedro de Manati-distrito de Indiana. 2021 - Sommo Mendoza, Andrea Solange (2023)
The present work developed in the community of San Pedro, district of Indiana was titled; Educational processes in the use of communal drinking water service. 2021. It had the objective of evaluating educational processes in the use of the communal drinking water service in the mentioned locality. These processes are represented with indicators. We worked with a sample of 36 users of this service. It is a descriptive, transversal work. The following results were reached: they do not maintain educational processes that benefit the good drinking water service, a situation that includes users and community leaders of San Pedro de Manatí. Education and culture were measured, it exhibits a regular level in sanitary education (61.4%), in sanitary habits (state of sanitation) it is considered regular (48.57% points), In operation and maintenance the service is at risk (23 points). In education and culture, there is a lack of training in wastewater management in the population (94.44%), which includes latrines; in the community college, health information is not shared with students (72.44%). (55.55%) consider that drinking water is a service, and the fee minimally covers the operating service (52.78%). In sanitary habits, there is no practice of disinfecting food preparation areas, as well as disposing of waste in buckets or bags; The way to store food and water is not correct, the presence of rodents and insects in the houses is observed. The animals are raised on pasture. For the operation and maintenance activity, they maintain a trained and salaried operator, the users have an endowment of 18 liters/bucket per person. Physicochemical and bacteriological analyzes are carried out annually, but the results are not known. In percentage terms, this operation is found (70%), saying that there are still indicators to improve to reach 100%.